NILAI INDEKS GLIKEMIK PADA BERBAGAI PEMANGKASAN DAUN DAN UMUR PANEN TALAS KIMPUL - Nugraha Ramadhan; Zulfadly Syarif; Indra Dwipa (Jurnal Agroekoteknologi, 2019)
ABSTRACTThe research was conducted from October 2017 to February 2018. The experimental material used in the research was Talas Kimpul. The research was factorial in the form of randomized block design. The aim of the study was to determine whether the treatment of pruning and different harvesting time the glycemic index value in Talas Kimpul. The treatments of leave pruning in this study consisted of; without pruning, pruning by leaving 4 leaves, and pruning by leaving 6 leaves. On the other hand, the harvest times treatment is on 6 months, 7 months, and 8 months. 9 respondents were tested for blood glucose. Fasting blood glucose examination results, 30, 60, 90, and 120 minutes after subjects consumed reference food (pure glucose) and test food (boiled taro from each treatment). Each treatment was given a span of 2 days to avoid bias from each food tested. The results showed that the glycemic index value of Talas Kimpul did not depend on the pruning and harvest times.